Feminist curiosity. Issue 9 (9th August 2021) - Zurn, Perry
Abstract: What is feminist curiosity? Or better yet, how is feminist curiosity practiced, where is it practiced, and with whom is it practiced? In this essay, I develop a philosophical account of feminist curiosity by drawing on direct contributions from the feminist philosophical tradition, but also by interweaving scattered testaments to feminist curiosity from critical race theory, intersex studies, disability studies, and trans studies. What surfaces in this inquiry is an account of feminist curiosity that goes far beyond the act of asking feminist questions. Feminist curiosity proper, I suggest, reconfigures not simply what gets asked, but with whom, where, and how inquiry happens. Feminist curiosity is rooted in companionship (with self and others), reorients time (a visionary future, but also a material past and present), and resists oppressive forms of inquiry such as spectacularization and the presumptions of access. As such, feminist curiosity is committed not only to a relational world but to a relational investigation of that world.